Pengaruh Komunikasi Pemasaran, Kepercayaan dan Penanganan Keluhan Terhadap Loyalitas Nasabah Pembiayaan Murabahah di BPRS Puduarta Insani - Widi Paratika Dewi; Syahrul Amsari (Universitas Islam Negeri Sumatera Utara, 2023)
This research was conducted with the aim of analyzing the effect of marketing communications, trust and complaint handling on customer loyalty in murabahah financing at BPRS Puduarta Insani. The research method used in this study is quantitative research and data collection techniques in this study using a questionnaire. The data analysis used in this research is data quality test, classic assumption test, multiple linear regression test, hypothesis test and determination test. Based on the results of the study, it shows that the Marketing Communicaion Variable (X1) has a positive and significant effect on the Customer Loyalty Variable of Murabahah Financing at BPRS Puduarta Insani (Y) with the acquisition of tcount (3,819) > ttable (1,989) with a significant value of 0,001 < 0,05, Variable Trust (X2) has a positive and significant effect on the Variable Costumer Loyalty of Murabahah Financing at BPRS Puduarta Insani (Y) with the acquisition of tcount (4,139) > ttable (1,989) with a significant value of 0,001 < 0,05, Complaint Handling Variable (X3) has a positive effect and significant to the Murabahah Financing Customer Loyalty Varible (Y) with the acquisition of tcount (14,525) > ttable (1,989) with a significant value of 0,001 < 0,05, test simultaneously on Marketing Communication Variables (X1), Trust (X2) and Complaint Handling (X3) states that there is a jointly significant effect on Customer Loyalty of Murabahah Financing at BPRS Puduarta Insani (Y) with the acquisition of Fcount (213,652) > ttable (2,71) with a significant level of 0,001.